The effect of nitrogen supplement on mycelial growth rate and fruiting substrate of Schizophyllum commune (split gill mushroom) - Abdullah, Nurul Jannah (2016)
Schizophyllum commune or commonly known as split gill mushroom is a type of widely distributed wood-decaying basidiomycetes that have been acknowledged for their medicinal properties. S. commune has been extensively cultured on the sawdust substrates which are common commercially used as fruiting substrate components for the cultivation of edible mushrooms in Malaysia. However the most suitable supplement of sawdust substrate to increase the growth rate of spawning and yield performance of S. commune is yet to be identified. In view of such issue, this research was conducted to investigate the effect of supplementation of nitrogen-sources for fruiting substrate of S. commune. Rice bran at different levels (0, 10, 20, 30, 40, and 50 %) was used as a supplement to evaluate the yield and biological efficiency of S. commune production. The experimental design used was Randomized Complete Block Design (RCBD) in which each treatment has four replicates. The mycelial growth rate, days required to fully colonize substrate bags, days for primordial formation, yield, and biological efficiency of the fruiting bodies of S. commune were evaluated. The result indicated that the 30 % of rice bran level was effective for producing viable fruiting bodies. The result indicated that increasing the supplementation level may resulted in less biological efficiency but throughout this experiment, it show that there was no significantly difference between 50 % and 30 % of rice bran. Thus, 30% of rice bran level was used as the best supplement in sawdust substrate due to the low quantity that were used to supplement the sawdust substrate compared to 50 % of rice bran level.